2016
DOI: 10.1177/1359105315589393
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and health-related quality of life in older people: Adaptive cognitive emotion regulation strategies as mediators

Abstract: This study examined whether adaptive cognitive emotion regulation strategies mediate the relationship between forgiveness and health-related quality of life in a sample of 350 Spanish people aged 55 years and older. Positive refocusing and positive reappraisal strategies partially mediated the relation between forgiveness and mental health. Thus, focusing on planning partially mediated the relation between forgiveness and physical health. Our findings contribute to an emerging understanding of the underlying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
16
1
2
Order By: Relevance
“…Health anxiety decreased with increasing adaptive cognitive emotion regulation. These results are consistent with the results of studies performed by Martin and Gitzen (26), Bardeen and Fergus (27), and Rey and Extremera (45). In explaining this finding, it can be stated that individuals who are unable to effectively control and monitor their emotional reactions experience more severe periods of sadness and anxiety that can lead to depression or anxiety (46).…”
Section: Discussionsupporting
confidence: 91%
“…Health anxiety decreased with increasing adaptive cognitive emotion regulation. These results are consistent with the results of studies performed by Martin and Gitzen (26), Bardeen and Fergus (27), and Rey and Extremera (45). In explaining this finding, it can be stated that individuals who are unable to effectively control and monitor their emotional reactions experience more severe periods of sadness and anxiety that can lead to depression or anxiety (46).…”
Section: Discussionsupporting
confidence: 91%
“…21 High levels of forgiveness have been found to be associated with high levels of health-related QOL in older people. 22 Gull et al (2013) found that the practice of forgiveness in daily life leads to satisfaction and subjective well-being that leads to a better QOL. 23 A systematic review by Akhtar et al (2016) verified that forgiveness helps reduce depression, anger and hostility, and stress and distress.…”
Section: Introductionmentioning
confidence: 99%
“…Coping generally refers to the cognitive and behavioral efforts (e.g., emotion regulation and problem solving) implemented to modulate internal or external demands that are appraised as taxing or exceeding personal resources (Endler & Parker, 1990;Garnefski et al, 2001;Lazarus & Folkman, 1984). Adaptive coping skills are thought to be critical for adaptation at old age (Gamrowska & Steuden, 2014;MacLeod et al, 2016), and have been associated with higher QoL (Hildon et al, 2010;León-Navarrete et al, 2017;Rey & Extremera, 2016). Two recently developed instruments that capture various cognitive (emotion regulation) and behavioral coping strategies are the Positive Appraisal Style Scale (PASS) and the Behavioral Coping Scale (BCS).…”
Section: Resilience Factorsmentioning
confidence: 99%